2008
DOI: 10.1111/j.1365-2109.2008.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the immunological and physiological parameters of the Pacific oysterCrassostrea gigascultured in Bahía de Macapule (Sinaloa, Mexico)

Abstract: Triploid Crassostrea gigas were cultured during 13 months in Nestier-type oyster trays. The impact of environmental parameters on the physiological and immunological parameters was evaluated. Temperature, salinity and seston were recorded monthly. Seventeen oysters were sampled monthly for immunological and condition index (CI) analyses. Samples were obtained as a haemolymph lysate supernatant (HLS). Protein content was determined using the Bradford method. The activity of hydrolytic enzymes was determined usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…In this study, the notably high level of protein concentration of A. japonicus CFS were found from December to the March of next year, suggesting that the immune condition of A. japonicus might fluctuate dramatically during this period. Besides, the variation in protein concentration in A. japonicus had significant negative correlation with water temperature, which is identical to the reports in the oysters C. gigas (Luna-Gonz alez et al 2008) and Crassostrea virginica (Chu & Peyre 1989), but opposite to the discovery in the clam Venerupis philippinarum (Soudant et al 2004), suggesting water temperature has crucial but species-specific effects on the physiological and immune condition of marine invertebrates. In addition, the variation in protein concentration in A. japonicus was significantly and positively correlated with DO.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In this study, the notably high level of protein concentration of A. japonicus CFS were found from December to the March of next year, suggesting that the immune condition of A. japonicus might fluctuate dramatically during this period. Besides, the variation in protein concentration in A. japonicus had significant negative correlation with water temperature, which is identical to the reports in the oysters C. gigas (Luna-Gonz alez et al 2008) and Crassostrea virginica (Chu & Peyre 1989), but opposite to the discovery in the clam Venerupis philippinarum (Soudant et al 2004), suggesting water temperature has crucial but species-specific effects on the physiological and immune condition of marine invertebrates. In addition, the variation in protein concentration in A. japonicus was significantly and positively correlated with DO.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the seasonal occurrences of some sea cucumber diseases like skin ulceration syndrome, fungal diseases and acute peristome oedema disease (Wang et al 2005) indirectly proved the speculation described above. Besides, the variation in protein concentration in A. japonicus had significant negative correlation with water temperature, which is identical to the reports in the oysters C. gigas (Luna-Gonz alez et al 2008) and Crassostrea virginica (Chu & Peyre 1989), but opposite to the discovery in the clam Venerupis philippinarum (Soudant et al 2004), suggesting water temperature has crucial but species-specific effects on the physiological and immune condition of marine invertebrates. Protein concentration of haemolymph is an important index that reflects the physiological and immune condition of marine invertebrates (Soudant, Paillard, Choquet, Lambert, Reid, Marhic, Donaghy & Birkbeck 2004).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Variations in CI outcome from multiple interactions of many factors, including food, temperature, and salinity, although the availability of food is considered as the main factor after the gametogenic cycle (Boscolo et al, 2003). Previous studies indicated that the CI of C. gigas did not have a direct relationship with reproduction and the 252 enhancements were combined with accumulation of energy reserves during autumn and winter when concentrations of POM were higher (Chávez-Villalba et al, 2007;Luna-González et al, 2008). This pattern was observed in populations reared at Sidi Moussa, since CI of oysters was significantly higher in winter (January-March 2015) with respect to oysters at Oualidia.…”
Section: Growthmentioning
confidence: 84%